Teaching children with autism to request items using audio scripts, interrupted chain procedure and sufficient exemplar training. (4th December 2020) - Wójcik, Marta; Eikeseth, Svein; Eldevik, Sigmund; Budzińska, Anna
Abstract: We examined whether an interrupting chain procedure with establishing operation (EO)‐absent and EO‐present trials and sufficient exemplar training was effective in teaching three preschool‐aged children with autism to request missing items. Children were taught to request missing items across three different skill domains (play, self‐help, and academic tasks), and audio scripts were used as prompts. We employed a non‐concurrent multiple‐baseline design across participants. All three participants learned to request missing items during EO‐present trials and to refrain from doing so during EO‐absent trials. The behavior transferred to untrained tasks, generalized to new people, and was maintained at follow‐up 3 months after the intervention.